Importance of English in the Media around the World - Archana , S. (Research Highlights in Language, Literature and Education Vol. 6, 2023)
Nelson Mandela once said that “Without language, one cannot talk to people and understand them; one cannot share their hopes and aspirations, grasp their history, appreciate their poetry, or savor their songs”. In this context, it is clear that language has its own significance which leads to the effective communication. English Language has its own importance in this fast rapid growing world as it has spread its roots throughout the globe by placing itself in the top priority by grabbing the titles as the Global Language or the International Language. In this process, the present study tries to emphasize the English Language and its importance in different spheres especially on Media. This chapter tries to explain the significance of the English language in the media, especially in India, which facilitates the learner and the reader in receiving tangible information. It also emphasizes on the acquisition of language, which is beneficial to improve the learners' understanding and also the language standard by preparing them to face the comprehensive world. In this fast growing globalized world, the media has taken over, in competing with the present trends and inventions. Media plays an immense role in influencing people. Whether the objective is to sell a product, communicate a significant case or to set the principles in today’s competitive society, they function with a massive power in facing this globalized world. Besides, with the advent of Globalization, there has been an enormous contribution of media to the humankind. The media plays a crucial role in getting the truth to society's citizens. By positioning itself as one of the effective tools, it has a deeply ingrained significance in the modern era. In the present generation, learning takes place within and outside the classroom. Media floats more information to the learners through the radio, newspapers, magazines, television, Internet etc., in addition to classroom teaching by using English as a medium of transmitting information. Thus, English in the media tries to bring a prolific transformation in the society.